Performance of non-invasive myocardial work to predict the first hospitalization for de novo heart failure with preserved ejection fraction (HFpEF). (4th February 2022) - Paolisso, P; Gallinoro, E; Mileva, N; Moya, A; Fabbricatore, D; Esposito, G; De Colle, C; Spapen, J; Heggermont, W; Collet, C; Van Camp, G; Vanderheyden, M; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): Dr. Paolisso, Dr. Esposito, Dr. Fabbricatore are supported by a research grant from the CardioPaTh PhD Program of University of Naples Federico II Background Non-invasive myocardial work (MW) is a validated index of left ventricular (LV) systolic performance, incorporating afterload and myocardial metabolism. The role of MW in predicting the first hospitalization for de novo heart failure with preserved ejection fraction (HFpEF) is still unknown. Purpose: To investigate the diagnostic performance of MW to predict the first de novo HFpEF hospitalization in ambulatory individuals with preserved LVEF. Methods Twenty-nine patients with trans-thoracic echocardiography performed at least 6 months before the first HFpEF hospitalization were compared with 29 matched controls. MW was derived as the area of pressure-strain loop using speckle-tracking and brachial artery blood pressure. Global work index (GWI), global constructive work (GCW), global wasted work (GWW), and global work efficiency (GWE) were collected. First HFpEF hospitalization and its combination with cardiovascular death (MACE) and all-cause of death (MAE) were assessed. Results At baseline, future HFpEF patients showed lower GWI, GCW, GWE and higher GWW than controls (all p < 0.05). At admission versus baseline, GWE significantly decreased, and GWW increased in the HFpEF group (p < 0.05), whereas no significant difference was observed in the controls over time. GWW, with a cut-off of 170 mmHg%, showed the largest AUC to predict first HFpEF hospitalization (AUC = 0.80, 95% CI 0.69–0.91, p < 0.001), MACE (AUC = 0.80, 95% CI 0.66–0.90, p < 0.001) and MAE (AUC = 0.79, 95% CI 0.62–0.88, p = 0.001). GWW > 170 mmHg% was associated with a 4-fold increase of MACE (HR = 4.5, 95% CI 1.59–13.12, p = 0.005) and a 3-fold higher risk of MAE (HR = 2.9, 95% CI 1.24–6.6, p = 0.014). Conclusions In ambulatory patients with preserved LVEF and risk factors, GWW showed high accuracy to predict the first HFpEF hospitalization and its combination with mortality. The GWW routine assessment may be clinically helpful in patients with dyspnea.